Konstantinov effect in helium II: Жидкий гелий - Melnikovsky, L.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We consider reflection of first and second sound waves by a rigid flat wall in helium II. A nontrivial dependence of the reflection coefficients on the angle of incidence is obtained. Sound conversion is predicted at slanted incidence.